2014
DOI: 10.3899/jrheum.131096
|View full text |Cite
|
Sign up to set email alerts
|

Causal Attributions about Disease Onset and Relapse in Patients with Systemic Vasculitis

Abstract: Objectives Patients vary in their beliefs related to the cause of serious illness. The impact of these beliefs among patients with systemic vasculitis is not known. This study aimed to describe causal attributions about disease-onset and relapse in systemic vasculitis and to examine whether causal beliefs a) differ by type of vasculitis; and b) are associated with negative health outcomes. Methods Patients with vasculitis were recruited to complete an online questionnaire. Categories of causal beliefs were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
0
9
1
Order By: Relevance
“…10 In the present assessment, we found that fewer than half of inflammatory SE etiologies were related to autoimmune mechanisms, which suggests that the role of autoimmunity among all SE cases, at least in adults, is somewhat limited. [27][28][29] We observed that inflammatory SE was significantly more refractory to initial antiepileptic treatment. Similarly, a recent review 24 reported 62 adult and 40 pediatric autoimmune SE published between 1992 and 2014, including those linked to antibodies directed against neuronal surface (NMDA, AMPA, g-aminobutyric acid [GABA] A and GABA B , CASPR2, DPPX), targeting intracellular antigens (GAD) or thyroid.…”
Section: Resultsmentioning
confidence: 91%
“…10 In the present assessment, we found that fewer than half of inflammatory SE etiologies were related to autoimmune mechanisms, which suggests that the role of autoimmunity among all SE cases, at least in adults, is somewhat limited. [27][28][29] We observed that inflammatory SE was significantly more refractory to initial antiepileptic treatment. Similarly, a recent review 24 reported 62 adult and 40 pediatric autoimmune SE published between 1992 and 2014, including those linked to antibodies directed against neuronal surface (NMDA, AMPA, g-aminobutyric acid [GABA] A and GABA B , CASPR2, DPPX), targeting intracellular antigens (GAD) or thyroid.…”
Section: Resultsmentioning
confidence: 91%
“…The process is usually activated in certain situations of serving or helping another person (Weiner 1980a), hence it is introduced in this study as a relevant lens to nurses emotional labour. The attribution process has been shown to affect interactions in various serviceproviding scenarios including health care (Morrow et al 2011, Grayson et al 2014, Weiss et al 2014. Its connection to nurses' emotional labour, however, has only been recently implied (Crego et al 2013) and yet to be fully clear.…”
Section: What Are the Key Findings?mentioning
confidence: 99%
“…The same nurse might engage deep acting in certain encounters and surface acting in others. The attribution process has been shown to affect interactions in various serviceproviding scenarios including health care (Morrow et al 2011, Grayson et al 2014, Weiss et al 2014. Attribution theory (Weiner 1982) suggests that individuals act as naive psychologists in their desire to understand causes of events.…”
Section: Introductionmentioning
confidence: 99%
“…Confusion is understandable given the multidimensional and complex etiology of insomnia, but may suggest that these survivors might particularly benefit from treatment modalities that include a strong psychoeducational component. Among chronically ill individuals, those who spoke with their doctors about their illness beliefs were less likely to ascribe their illness to "chance," (Grayson et al, 2014) and educational interventions are capable of shifting individuals' causal attributions of illness (Abood, Black, & Feral, 2003;Boling, Laufman, Lynch, & Weinberg, 2005). Future research is warranted to understand whether these "unsure" individuals demonstrated better treatment response to CBT-I, which heavily emphasizes education, or acupuncture, which does not rely on individuals' understanding of their insomnia.…”
Section: Discussionmentioning
confidence: 99%